2019
DOI: 10.1038/s41586-019-1410-1
|View full text |Cite|
|
Sign up to set email alerts
|

Absence of NKG2D ligands defines leukaemia stem cells and mediates their immune evasion

Abstract: Data availability statement. All data generated are included in the published article and in the Supplementary Information. Gene expression data that support the findings of this study have been deposited in the Gene Expression Omnibus under accession numbers GSE127200 and 127959. All data are also available from the authors on reasonable request.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
243
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 290 publications
(255 citation statements)
references
References 47 publications
10
243
1
1
Order By: Relevance
“…Low or absent expression of NK cell‐activating receptor ligands (NKG2DLs) of the MIC and ULBP families, as well as secretion of soluble NKG2DLs in AML, is well established as a strategy for immune escape employed by leukemia cells (Nowbakht et al , ; Hilpert et al , ). However, Paczulla et al () here provide the first demonstration that the absence of NKG2DLs is a defining characteristic of LSCs and that PARP1 inhibition can restore NKG2DL expression thus sensitivity to NK cell immune surveillance. Interestingly, the investigators also found that previously reported stimuli to promote NKG2DL expression in leukemia cells, such as all‐trans retinoic acid (ATRA), valproic acid, and azacitidine, were not able to enhance NKG2DL expression by LSCs (Paczulla et al , ).…”
Section: Parp1 Inhibition Restores Nk Cell Immune Surveillance In Leumentioning
confidence: 64%
See 4 more Smart Citations
“…Low or absent expression of NK cell‐activating receptor ligands (NKG2DLs) of the MIC and ULBP families, as well as secretion of soluble NKG2DLs in AML, is well established as a strategy for immune escape employed by leukemia cells (Nowbakht et al , ; Hilpert et al , ). However, Paczulla et al () here provide the first demonstration that the absence of NKG2DLs is a defining characteristic of LSCs and that PARP1 inhibition can restore NKG2DL expression thus sensitivity to NK cell immune surveillance. Interestingly, the investigators also found that previously reported stimuli to promote NKG2DL expression in leukemia cells, such as all‐trans retinoic acid (ATRA), valproic acid, and azacitidine, were not able to enhance NKG2DL expression by LSCs (Paczulla et al , ).…”
Section: Parp1 Inhibition Restores Nk Cell Immune Surveillance In Leumentioning
confidence: 64%
“…However, Paczulla et al () here provide the first demonstration that the absence of NKG2DLs is a defining characteristic of LSCs and that PARP1 inhibition can restore NKG2DL expression thus sensitivity to NK cell immune surveillance. Interestingly, the investigators also found that previously reported stimuli to promote NKG2DL expression in leukemia cells, such as all‐trans retinoic acid (ATRA), valproic acid, and azacitidine, were not able to enhance NKG2DL expression by LSCs (Paczulla et al , ). Both IFNα and IL‐15 have also been demonstrated to enhance NK cell cytotoxic function as well as to promote expression of cell surface NKG2DLs on leukemia cells (Szczepanski et al , , Zhang et al , ); however, these were not explored in the current study.…”
Section: Parp1 Inhibition Restores Nk Cell Immune Surveillance In Leumentioning
confidence: 64%
See 3 more Smart Citations